The study of end user satisfaction at PFI building / Mohd Hafiz Mohamad - Mohamad, Mohd Hafiz (2015)
Nowadays, the construction of the Private of Finance Initiative (PFI) are increases according to the government planning in Ninth Malaysian Plan 2006-2010, from the large numbers of privatized projects were in the construction sector (42.9%) in the period. Sometimes, the performance of PFI building depend on the efficiency of the facilities management program of the building itself. The good facilities management program can give the full satisfaction for the consumer or building user. The studies to develop the end user satisfaction framework were focusing in the context the Facilities Management (FM) performance of the PFI building. The challenging have contribute in building performance are indoor air quality, quality of building services, workplace, sustainable of building, information system and service delivery. The process of the study by used the document review and questionnaires. Based on the analysis that has been obtain from the questionnaire, mostly agree with the challenging factor that been asked which arise in the literature review. Facilities management should also maintain the maximum level to provide the good performance and quality for the end user in PFI building.